2022
DOI: 10.3390/cancers14153658
|View full text |Cite
|
Sign up to set email alerts
|

Total Neoadjuvant Therapy for Rectal Cancer in the CAO/ARO/AIO-12 Randomized Phase 2 Trial: Early Surrogate Endpoints Revisited

Abstract: Background: Early efficacy outcome measures in rectal cancer after total neoadjuvant treatment are increasingly investigated. We examined the prognostic role of pathological complete response (pCR), tumor regression grading (TRG) and neoadjuvant rectal (NAR) score for disease-free survival (DFS) in patients with rectal carcinoma treated within the CAO/ARO/AIO-12 randomized phase 2 trial. Methods: Distribution of pCR, TRG and NAR score was analyzed using the Pearson’s chi-squared test. Univariable analyses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Nor is it known if chemotherapy should be provided after radiation (consolidation) or before (induction). At least two trials indicate that CRT first results in better oncological outcome ( 93 , 94 , 98 ). It is not known whether triple chemotherapy, as used in PRODIGE-23 ( 34 ) or GRECCAR-4 ( 91 ) or a doublet as used in the other trials, is advantageous.…”
Section: Total Neoadjuvant Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Nor is it known if chemotherapy should be provided after radiation (consolidation) or before (induction). At least two trials indicate that CRT first results in better oncological outcome ( 93 , 94 , 98 ). It is not known whether triple chemotherapy, as used in PRODIGE-23 ( 34 ) or GRECCAR-4 ( 91 ) or a doublet as used in the other trials, is advantageous.…”
Section: Total Neoadjuvant Treatmentmentioning
confidence: 99%
“…It is, thus, possible to select a group of patients whose tumours are sensitive to chemotherapy and omit CRT with its late toxicity. This may constitute an argument for starting with chemotherapy although this sequence appeared worse in two trials ( 93 , 94 , 98 ).…”
Section: Total Neoadjuvant Treatmentmentioning
confidence: 99%
“…Randomized phase III trials examining the addition of oxaliplatin concurrently with LCCRT provided useful data for benchmarking [5][6][7][8][9][10]26,27]. We also considered several relevant randomized phase II trials investigating NACT [18,19,[28][29][30][31][32][33][34][35][36][37][38][39][40], prospective phase II trials, and metaanalyses of varying quality examining TNT [41][42][43][44][45][46][47][48][49][50].…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%
“…As mentioned above, the timing of surgery after TNT is variable: 6-8 weeks (STELLAR), 4-12 weeks (Memorial Sloan Kettering), 2-4 weeks (RAPIDO), or 6-12 weeks (CAO/ARO/AIO-12). Therefore, the optimal timing is not established in clinical practice [9,10,12,15,22,36]. In terms of tumor resection, several studies have reported high rates of pCR, tumor downstaging, and R0 resection, whereas others have not found significant differences in R0 resection [34].…”
Section: Evaluation Of Responsementioning
confidence: 99%